'Very much like any other Japanese RPG you've ever played': Using undirected topic modelling to examine the evolution of JRPGs' presence in anglophone web publications. Issue 2 (1st June 2018) - Pelletier-Gagnon, Jérémie
What types of discourses characterize Japanese role-playing games (JRPGs) as a genre of video games? Why is the genre so difficult to define, and why has it become polarizing within the gaming community? This article suggests an outline of the evolution of the discourse surrounding JRPGs based on a macroanalysis of the anglophone online gaming press. Using undirected topic modelling text mining methodology to analyse a corpus of 2053 JRPG reviews gathered from ten different online journalistic outlets posted between 1992 and 2014, this article demonstrates the circumstances of the gradual introduction of the term Japanese role-playing games in online publication, first as an extension of other examples Japanese pop culture in the late 1990s and early 2000s, and subsequently as its own genre appropriated by anglophone gaming culture in the mid-2000s onwards and subjected to this community's particular regime of values.